HBR guide to remote work. - Harvard Business Review Press (Boston, Massachusetts : Harvard Business Review Press, 2021)
The HBR Guide to Remote Work provides practical tips and advice to help you stay productive, avoid distractions, and collaborate with your team, despite the distance that separates you. You'll learn to: Create a regular work-from-home routine Identify the right technology for your needs Run better virtual meetings Avoid burnout and video-call fatigue Manage remote employees Conduct difficult conversations when you can't meet in person Arm yourself with the advice you need to succeed on the job, with the most trusted brand in business. Packed with how-to essentials from leading experts, the HBR Guides provide smart answers to your most pressing work challenges.
Intro -- What You'll Learn -- Contents -- Introduction -- Section 1: Getting Work Done -- Ch. 1: How to Stay Focused When You're Working from Home -- Ch. 2: Things to Buy, Download, or Do When Working Remotely -- Ch. 3: Working from Home When You Have Kids -- Ch. 4: How to Transistion Between Work Time and Personal Time -- Ch. 5: Staying Motivated in a Remote Job -- Section 2: Navigating Common Challenges -- Ch. 6: Working Smoothly with a Virtual Boss -- Ch. 7: How to Resolve a Conflict with a Remote Colleague -- Ch. 8: 4 Ways to Demonstrate Your Value-Remotely -- Ch. 9: Starting a New -- Section 3: Caring for Your Mental and Emotional Health -- Ch. 10: 3 Tips to Avoid Work-from-Home Burnout -- Ch. 11: Resilience Is About How You Recharge, Not How You Endure -- Ch. 12: 5 Tips to Reduce Screen Time While You're Working from Home -- Ch. 13: How to Combat Video Call Fatigue -- Section 4: Thriving in Virtual Meetings -- Ch. 14: What Everyone Should Know About Running Virtual Meetings -- Ch. 15: Elevate Your Presence on a Video Call -- Ch. 16: Break Up Your Brainstorming Sessions -- Ch. 17: Virtual Off-Sites That Work -- Ch. 18: Stop Zoning Out in Zoom Meetings -- Section 5: Being the Boss -- Ch. 19: How to Manage Remote Direct Reports -- Ch. 20: 5 Questions (Newly) Virtual Leaders Should Ask Themselves -- Ch. 21: Make Yourself Available to Remote Employees -- Ch. 22: How to Keep Your Team Motivated, Remotely -- Ch. 23: Tips for Coaching Someone Virtually -- Ch. 24: How to Manage a Remote Employee Who's Struggling to Perform -- Section 6: Solvinh Problems on a Remote Team -- Ch. 25: How to Collaborate Effectively If Your Team Is Remote -- Ch. 26: Managing a Team Across 5 Time Zones -- Ch. 27: How to Raise Sensitive Issues with Your Remote Team -- Ch. 28: Ideas for Helping Remote Colleagues Bond -- Index.
"Be more productive, set boundaries, connect with your team"--Cover.
Description based on online resource; title from digital title page (viewed on March 04, 2021).
Master record variable field(s) change: 050
Keywords: Telecommuting; Virtual reality in management; Electronic books; Telecommuting; Virtual reality in management; elektronické knihy; electronic books